Americae sive novi orbis, nova descriptio. - Ortelius, Abraham, 1527-1598 ([Aegid], 1570)
Map shows North America and South America as understood during the late sixteenth century. Political boundaries are indicated by coloration in different regions of each continent. Relief shown pictorially. No scale indicated.